EXPERIMENTAL INFECTION OF RABBITS WITH Dictyocaulue filaria - PATHOLOGICAL FINDINGS - M. AL-Darraji, A.; T. AL-Dabagh, A.; A. Ali, S. (The Iraqi Journal of Veterinary Medicine, 1990)
This experiment was designed to evaluate rabbite as an experimental animal for Dictyocaulue filaria (of sheep erigin) infection, using parasitological and pathological parameters. Fifteen adult rabbits of local breed were divided into 3 equal groups and given orally 1000. 2500 and 5000 infective larvae per animal respectively. One animal from each group was sacrificed 6,10,15,21 and 30 days pest infection. Results showed that most rabbits of all groups resisted infection with D. filaria as evidenced from the clinical and pathe logical findings and the reduced numbers of the recovered parasites and their stunted growth. It is concluded that rabbite are not good laboratory animal model for reproduction of D.filaria infection